Criminal Law and Juvenile Delinquency: An Analysis of Legal Approaches to Juvenile Offenders - Widowati, Widowati (CV. Era Digital Nusantara, 2025)
Juvenile delinquency is a critical issue in criminal law, involving young individuals who engage in illegal activities. The legal system's response to juvenile offenders varies across countries, shaped by considerations of rehabilitation, punishment, and social reintegration. This article explores the legal frameworks and policies that address juvenile delinquency, focusing on the distinction between how criminal behavior is treated in children and adults. It examines the principles guiding juvenile justice systems, with a focus on legal protections, juvenile rights, and international standards. The study investigates the factors contributing to juvenile crime, including social, economic, and familial influences, and the impact of legal interventions on preventing recidivism. By reviewing existing literature on juvenile crime and analyzing case studies from both Indonesia and abroad, the article highlights the evolving trends in juvenile justice, emphasizing restorative justice, diversion programs, and alternatives to incarceration. The aim is to propose a balanced approach that considers the need for both accountability and rehabilitation in dealing with young offenders, ensuring their reintegration into society as productive citizens.